An Integrated Caco-2TC7cells/biosensors Device for the Real Time Monitoring of Intestinal Glucose and Polyphenols Absorption and Hypoglycemic Effect of Phytochemicals. (2017) - Antonio, Barberis; Antonella, Garbetta; Angela, Cardinali; Gianfranco, Bazzu; Isabella, D'Antuono; Gaia, Rocchitta; Angela, Fadda; Vito, Linsalata; Guy, D'Hallewin; Andrea, Serra Pier; Fiorenza, Minervini
Abstract: An integrated device, for real-time monitoring of glucose and phenols absorption, that consists of a sensors/biosensors system (SB) and a Caco-2TC7 human intestinal cell culture, is shown here. The SB was made of a glucose oxidase-based biosensor, a sentinel platinum sensor, a laccase/tyrosinase-based biosensor and a sentinel carbon sensor located in the basolateral compartment (BC) of a cell culture plate. This system was able to monitor the glucose absorption and the hypoglycemic effect induced by different polyphenols and could be proposed to provide an effective strategy to manage postprandial hyperglycemia with natural compounds.